2013
DOI: 10.3758/s13428-013-0357-7
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic motivation and attentional capture from gamelike features in a visual search task

Abstract: In psychology research studies, the goals of the experimenter and the goals of the participants often do not align. Researchers are interested in having participants who take the experimental task seriously, whereas participants are interested in earning their incentive (e.g., money or course credit) as quickly as possible. Creating experimental methods that are pleasant for participants and that reward them for effortful and accurate data generation, while not compromising the scientific integrity of the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(113 citation statements)
references
References 39 publications
10
101
0
2
Order By: Relevance
“…Psychologists have a history of using games and game-like interfaces to make experiments more palatable to participants (e.g., Anguera et al, 2013;Boot et al, 2010;Mané & Donchin, 1989;Miranda & Palmer, 2014), and mobile devices offer an exciting new means to crowd source an experiment in a game-like form.…”
Section: Drivers Of Prediction Accuracy In World Politicsmentioning
confidence: 99%
“…Psychologists have a history of using games and game-like interfaces to make experiments more palatable to participants (e.g., Anguera et al, 2013;Boot et al, 2010;Mané & Donchin, 1989;Miranda & Palmer, 2014), and mobile devices offer an exciting new means to crowd source an experiment in a game-like form.…”
Section: Drivers Of Prediction Accuracy In World Politicsmentioning
confidence: 99%
“…In our task, the participant's points score was displayed at the bottom of the screen throughout (see Figure 2C). The scoring system was very similar to that used in our previous study (Lumsden, Skinner, et al, 2016), which in turn was based on that used by (Miranda & Palmer, 2014). The scoring system also incorporates findings of (Guitart-Masip et al, 2012) who found that subjects were much more successful in learning active (go) choices when rewarded for them, and passive choices (stop) when punished.…”
Section: Effect Of Gamification On Attritionmentioning
confidence: 83%
“…The following questions were based on those used in previous studies (Hawkins et al, 2013;Lumsden, Skinner, et al, 2016;Miranda & Palmer, 2014), and were presented in a random order: (1)…”
Section: Enjoyment and Engagement Questionnaire The Enjoyment And Enmentioning
confidence: 99%
“…Miranda and Palmer (2014). The total score, high score, and streak counter encouraged implicit social competition between participants.…”
Section: Previous Work On Attentional Capturementioning
confidence: 98%
“…Despite the fact that color was irrelevant to the task, the visual system prioritized the color previously associated with reward and thus allocated attention to it, causing slower RTs on those trials. Miranda and Palmer (2014) adapted the Anderson, et al (2011) paradigm and turned it into a visual search "game." During the training phase of the experiment, participants were awarded points on each trial depending on their performance.…”
Section: Previous Work On Attentional Capturementioning
confidence: 99%